The Effects of Ivermectin on Brugia malayi Females In Vitro: A Transcriptomic Approach - Ballesteros, Cristina; Tritten, Lucienne; O’Neill, Maeghan; Burkman, Erica; Zaky, Weam I.; Xia, Jianguo; Moorhead, Andrew; Williams, Steven A.; Geary, Timothy G. (PLOS Neglected Tropical Diseases, 2016)
Background Lymphatic filariasis and onchocerciasis are disabling and disfiguring neglected tropical diseases of major importance in developing countries. Ivermectin is the drug of choice for mass drug administration programs for the control of onchocerciasis and lymphatic filariasis in areas where the diseases are co-endemic. Although ivermectin paralyzes somatic and pharyngeal muscles in many nematodes, these actions are poorly characterized in adult filariae. We hypothesize that paralysis of pharyngeal pumping by ivermectin in filariae could result in deprivation of essential nutrients, especially iron, inducing a wide range of responses evidenced by altered gene expression, changes in metabolic pathways, and altered developmental states in embryos. Previous studies have shown that ivermectin treatment significantly reduces microfilariae release from females within four days of exposure in vivo, while not markedly affecting adult worms. However, the mechanisms responsible for reduced production of microfilariae are poorly understood. Methodology/Principal Findings We analyzed transcriptomic profiles from Brugia malayi adult females, an important model for other filariae, using RNAseq technology after exposure in culture to ivermectin at various concentrations (100 nM, 300 nM and 1 μM) and time points (24, 48, 72 h, and 5 days). Our analysis revealed drug-related changes in expression of genes involved in meiosis, as well as oxidative phosphorylation, which were significantly down-regulated as early as 24 h post-exposure. RNA interference phenotypes of the orthologs of these down-regulated genes in C. elegans include “maternal sterile”, “embryonic lethal”, “larval arrest”, “larval lethal” and “sick”. Conclusion/Significance These changes provide insight into the mechanisms involved in ivermectin-induced reduction in microfilaria output and impaired fertility, embryogenesis, and larval development.